Highly boosting the interlaminar shear strength of CF/PEEK composites via introduction of PEKK onto activated CF. (September 2018) - Hassan, Elwathig A.M.; Ge, Dengteng; Yang, Lili; Zhou, Jianfeng; Liu, Mingxia; Yu, Muhuo; Zhu, Shu
Graphical abstract: Highlights: Interlaminar shear strength (ILSS) and flexural strength and modulus of CF/PEEK composites remarkably improved after modifications. The strong adhesion can be ascribed mainly to formed hydrogen bonding between PEKK and CF and good compatibility of PEKK and PEEK matrix. These methods are quite easy to handle and can be applied to produce large size of composite materials containing continuous CF. Abstract: Due to poor wettability and low reactivity, the interfacial adhesions between CF and PEEK matrix are relatively weak, significantly affecting mechanical performances of composites, especially the interlaminar shear strength. This study focuses on improvement of fiber-matrix interfacial interactions for CF/PEEK composites via introducing interfacial layers of polyertherketoneketone (PEKK) on activated CF. This method takes advantage of hydrogen bond between PEKK and activated CF, as well as good compatibility between PEKK and PEEK. As a result, interlaminar shear strength, flexural strength and modulus of CF/PEEK composites increased by 70%, 37% and 48%, respectively. SEM observations on fractured surfaces of composites indicated that dominant failure mechanisms shifted from fiber-matrix debonding to deformation of interfacial layers and breakage in resin. This modification method is easy to handle and can be applied to produce large size of composite materials containing continuous CF or CF fabrics, showing potentials in industrial applications.